Efficacy of Vaccination in Preventing Pulmonary Infections in Interstitial Lung Disease (ILD) Patients - Rafique, Iqra; Ahmad, Muhammad Ayaz; Talal, Muhammad; Khalil, Saira (Indus Journal of Bioscience Research, 2025)
Background: Patients suffering from interstitial lung disease (ILD) are at increased risk for developing pulmonary infections, especially in the setting of concurrent immunosuppression. While pneumococcal and influenza vaccinations are advised for this population, their implementation in clinical practice is still partial. To evaluate the effectiveness of influenza and pneumococcal vaccination in preventing pulmonary infections and associated complications among ILD patients. Methods: A retrospective observational study was carried out at Jinnah Hospital, Lahore from June 2024 to December 2024 involving 72 ILD patients, whom were divided into 2 groups: vaccinated (n=38) and unvaccinated (n=34). Relevant clinical history, demographic details, vaccination status, and infection outcomes were collected and analyzed. The primary outcome was defined as pulmonary infection within the last 12 months and secondary outcomes included overall hospitalization and ICU admission. Results: Among the vaccinated patients, pulmonary infections were significantly less common (15.8%) in comparison to unvaccinated patients (50%, p<0.001). Infection related hospitalization was also lower in the vaccinated group (5.3% vs. 23.5%, p = 0.011). No ICU admissions were documented among the vaccinated patients as opposed to the unvaccinated patients (0% vs. 8.8%, p = 0.041). Conclusion: Influenza and pneumococcal vaccination amalgamates both the risk and severity of developing respiratory infections within ILD sufferers. Routine immunization is highlighted with particular focus as the preferred proactive approach in tempering ILD dynamics.